Appraisal of inflammation‐based prognostic scores in patients with unresectable perihilar cholangiocarcinoma. (30th August 2016) - Okuno, Masataka; Ebata, Tomoki; Yokoyama, Yukihiro; Igami, Tsuyoshi; Sugawara, Gen; Mizuno, Takashi; Yamaguchi, Junpei; Nagino, Masato
Abstract: Background: Inflammation‐based prognostic scores are useful prognostic indicators for several types of cancer. The aim of this study was to evaluate whether the scores predict survival impact in unresectable perihilar cholangiocarcinoma. Methods: The modified Glasgow Prognostic Score (mGPS), Neutrophil Lymphocyte Ratio (NLR), Platelet Lymphocyte Ratio, and Prognostic Nutritional Index, were retrospectively assessed in 219 patients with unresectable perihilar cholangiocarcinoma. Results: Of the four scores evaluated, mGPS and NLR demonstrated prognostic value, whereas the remaining two systems did not. The median survival time (MST) of patients with a mGPS of 0 and NLR of 0 or 1 were significantly better than that of patients with a mGPS of 1 or 2 and NLR of 2 (12.3 vs. 4.8 months, P  < 0.001, and 10.5 vs. 4.4 months, P  = 0.001). Multivariate analysis revealed that both mGPS and NLR were independent prognostic factors. The combination of mGPS and NLR stratified survival well: the MST was 12.8 months in patients with a mGPS of 0 and NLR of 1 or 2, while only 3.0 months in patients with a mGPS of 1 or 2 and NLR of 2. Conclusions: Both mGPS and NLR are independent prognostic factors and pivotal in refining patient stratification in unresectable perihilar cholangiocarcinoma. Abstract : Highlight Okuno and colleagues retrospectively assessed four inflammation‐based prognostic scores in 219 patients with unresectable perihilar cholangiocarcinoma. Both the modified Glasgow Prognostic Score (mGPS) and Neutrophil Lymphocyte Ratio (NLR) were independent prognostic factors and in combination they stratified survival well, indicating that these scoring systems are pivotal in refining patient stratification.